Prediction of mechanical properties of human rib cortical bone using fractal dimension. Issue 5 (6th July 2021) - Velázquez-Ameijide, Juan; García-Vilana, Silvia; Sánchez-Molina, David; Llumà, Jordi; Martínez-González, Eva; Rebollo-Soria, M. Carmen; Arregui-Dalmases, Carlos
Abstract: A large number of post mortem human subjects was used to investigate the relation between the micro-structure of rib cortical bone and the mechanical properties using Fractal Dimension. Uniaxial tensile tests were performed on coupons of rib cortical bone. Tensile strength, yield stress, Young's Modulus, maximum strain, and work to fracture were determined for each coupon. Fractal dimension was computed using CT images and Digital Image Correlation procedures. A highly significant effect of fractal dimension in the mechanical properties was found. In addition, the variation in mechanical properties was found to be adequately represented by Generalized Extreme Value type distributions.